Modeling the microbial growth of two Escherichia coli strains in a multi-substrate environment - Poccia,M. E. (2014)
The microbial growth in multi-substrate environments may be viewed as an optimal resources allocation problem. The optimization aims at maximizing some biological objective like the biomass growth. The models developed using this hypothesis are called "cybernetic" and they represent the complex cell structure as an optimizing function that regulates the intracellular enzymatic machinery. In this work, a cybernetic model was developed to represent the growth of two E. coli strains (JM 109 and BL 21 -DE3-) on a medium containing glucose and glycerol as carbon and energy sources. The model was able to accurately simulate the biomass growth, the substrates consumption and the growth-rate profiles.